Heavy metals in small ruminant’s milk from Algerian area steppe - Bouzidi, A. (2018)
The total contents and distributions between soluble and colloidal phases of heavy metals (Pb, Cd and Cr) in milk of two ewe’s breed (Ouled-Djellal and Rumbi) (n = 20 each) and one local goat (n = 10) reared in Algerian area steppe, were evaluated. Ewes and goats were conducted in the same herd with similar housing and feeding. All animals were pastured in non-polluted region of Djelfa. Individual milk samples were collected three times during spring season and analyzed for their heavy metal contents. Ewe’s milk exhibited higher (P ≤ 0.001) levels of Pb and Cd than goat’s milk but lower (P ≤ 0.001) value of Cr. The average Pb and Cd contents were 0.181 ± 0.062 ppm and 0.061 ± 0.021 ppm for ewe’s milk and 0.070 ± 0.023 and 0.012 ± 0.004 for goat’s milk respectively, which was considered as tolerable levels for human consumption. The concentrations of Cr were 0.054 ± 0.023 ppm and 0.131 ± 0.058 ppm for ewe and goat milks, respectively. There was no significant difference between the two breeds of Algerian ewe’s milk. Theses toxic elements were not in dangerous concentrations.